(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study developed and evaluated the Innovative Car Air Conditioning Trainer as an instructional prototype designed to enhance technical-vocational education in refrigeration and air conditioning technology. Guided by a developmental research design, the project progressed through three phases: design, construction, and evaluation. The trainer was conceptualized to integrate electrical protection devices, subsystem isolation switches, and digital monitoring instruments, thereby simulating the operational dynamics of an automotive air conditioning system. Fabrication involved the assembly of mechanical and electrical subsystems to replicate real-world RAC operations, while evaluation was conducted by faculty experts from the Bachelor of Science in Refrigeration and Air Conditioning Technology and Bachelor in Industrial Technology major in Heating, Ventilation, and Air Conditioning Technology (BIndTech HVACRT) programs at Zamboanga Peninsula Polytechnic State University. Using a structured survey instrument and four-point Likert scale, results revealed high levels of acceptability in terms of design, functionality, and instructional relevance, with mean ratings ranging from 3.8 to 4.0. Findings confirm that the trainer effectively bridges theoretical knowledge with hands-on practice, aligns with TESDA competency standards, and supports modular learning and fault simulation for enhanced student engagement. The study concludes that the prototype is both acceptable and effective as an instructional tool, with potential for replication, scaling, and further innovation to strengthen competency-based technical-vocational education.